2017
DOI: 10.1155/2017/2694261
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Prevents H2O2‐Induced Apoptosis via the PI3K/Akt Pathway in Rat Nucleus Pulposus Intervertebral Disc Cells

Abstract: Icariin is a prenylated flavonol glycoside derived from the Chinese herb Epimedium sagittatum. This study investigated the mechanism by which icariin prevents H2O2-induced apoptosis in rat nucleus pulposus (NP) cells. NP cells were isolated from the rat intervertebral disc and they were divided into five groups after 3 passages: (A) blank control; (B) 200 μM H2O2; (C) 200 μM H2O2 + 20 μM icariin; (D) 20 μM icariin + 200 μM H2O2 + 25 μM LY294002; (E) 200 μM H2O2 + 25 μM LY294002. LY294002 is a selective inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In the present study, we established an in vitro model for oxidative stress analysis in NPCs. Many studies have suggested that H 2 O 2 could induce oxidative stress injury, inflammatory response, apoptosis, matrix reduction, and, finally, degeneration of NPCs [ 16 18 ]. Consistently, our study identified the degenerative role of H 2 O 2 and established an in vitro model for oxidative stress analysis in NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we established an in vitro model for oxidative stress analysis in NPCs. Many studies have suggested that H 2 O 2 could induce oxidative stress injury, inflammatory response, apoptosis, matrix reduction, and, finally, degeneration of NPCs [ 16 18 ]. Consistently, our study identified the degenerative role of H 2 O 2 and established an in vitro model for oxidative stress analysis in NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that icariin treatment significantly induces the phosphorylation of AKT serine/threonine kinase 1 (AKT) and extracellular signal-regulated kinase (ERK) in dopaminergic EMS 23.5 cells ( 8 ). Deng et al ( 9 ) have also reported that icariin significantly upregulates the level of phosphorylated (p)-AKT in rat nucleus pulposus cells. As the phosphorylation of AKT and ERK are closely associated with the migration and proliferation of keratinocytes ( 10 ), it is logical to hypothesize that icariin could promote keratinocyte migration and proliferation, thus exerting a beneficial effect on wound healing.…”
Section: Introductionmentioning
confidence: 96%
“…A large number of in vitro and in vivo studies suggested that ICA could scavenge reactive oxygen species (ROS) [ 20 ] and exert antioxidative function in protecting the brain and heart [ 21 23 ]. Furthermore, ICA demonstrated other extensive pharmacological effects such as antiapoptosis effect, reproductive effect, anti-inflammation effect, and immunoprotective effect [ 24 , 25 ]. Due to its extensive cell protective effects, we hypothesized that ICA could be used in cryopreservation of NPMSCs.…”
Section: Introductionmentioning
confidence: 99%